2016
DOI: 10.1620/tjem.238.143
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26b Enhances the Radiosensitivity of Hepatocellular Carcinoma Cells by Targeting EphA2

Abstract: Sensitizing hepatocellular carcinoma (HCC) cells to irradiation is important to achieve satisfactory therapeutic effect with low-dose radiotherapy. Erythropoietin-producing hepatocellular carcinoma A2 (EphA2) is a member of the Eph receptor family that constitutes the largest family of tyrosine kinase receptors. EphA2 overexpression is one of the poor prognostic factors in many progressive cancers. Importantly, EphA2 is a potential target of microRNA-26b (miR-26b), and miR-26b expression is downregulated in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Studies demonstrated that miR‐26b could regulate HCC epithelial‐mesenchymal transition and metastasis through targeting USP9X and SMAD1 . Li et al reported that miR‐26b could inhibit HCC cell invasion and migration by directly binding to gene EphA2 . In addition, miR‐26b was reported to enhance the chemosensitivity of HCC cells by targeting TAK1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrated that miR‐26b could regulate HCC epithelial‐mesenchymal transition and metastasis through targeting USP9X and SMAD1 . Li et al reported that miR‐26b could inhibit HCC cell invasion and migration by directly binding to gene EphA2 . In addition, miR‐26b was reported to enhance the chemosensitivity of HCC cells by targeting TAK1 .…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Li et al reported that miR-26b could inhibit HCC cell invasion and migration by directly binding to gene EphA2. 28 In addition, miR-26b was reported to enhance the chemosensitivity of HCC cells by targeting TAK1. 13 Thus, these findings suggest that miR-26b plays a crucial role in HCC as a tumor-suppressing miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another miRNA family, miR‐26, is found to be profoundly involved in carcinogenesis, epithelial mesenchymal transition, and drug resistance in cancer cells [10–12]. MiR‐26b, a critical member of this family, is downregulated in multiple cancer cell lines and human carcinoma tissues [13–15]; while transfection with its mimic can inhibit proliferation and migration, decrease chemo‐resistance, and trigger apoptosis in various tumors, indicating the tumor suppressive effect of this miRNA [16–20]. Regarding lung cancer, a previous study confirmed that the expression of miR‐26b is downregulated in non‐small cell lung cancer (NSCLC) tissues, and may serve as a useful marker for the diagnosis and prognosis of NSCLC patients [14].…”
Section: Introductionmentioning
confidence: 93%
“…The expression profiles and the result of dual reporter assay revealed the interrelationship of miR-26b and EphA2. Transfection of miR-26b mimics or EphA2-shRNA leading to radiosensitization of 97H HCC cells and overexpression of EphA2 can protect 97H HCC cells from irradiation [79].…”
Section: Radiation-associated Mirnas In Hccmentioning
confidence: 99%